Group clinics for young adults with diabetes in an ethnically diverse, socioeconomically deprived setting (TOGETHER study): protocol for a realist review, co-design and mixed methods, participatory evaluation of a new care model. Issue 6 (21st June 2017) - Papoutsi, Chrysanthi; Hargreaves, Dougal; Colligan, Grainne; Hagell, Ann; Patel, Anita; Campbell-Richards, Desirée; Viner, Russell M; Vijayaraghavan, Shanti; Marshall, Martin; Greenhalgh, Trisha; Finer, Sarah
Abstract : Introduction: Young adults with diabetes often report dissatisfaction with care and have poor diabetes-related health outcomes. As diabetes prevalence continues to rise, group-based care could provide a sustainable alternative to traditional one-to-one consultations, by engaging young people through life stage-, context- and culturally-sensitive approaches. In this study, we will co-design and evaluate a group-based care model for young adults with diabetes and complex health and social needs in socioeconomically deprived areas. Methods and analysis: This participatory study will include three phases. In phase 1, we will carry out a realist review to synthesise the literature on group-based care for young adults with diabetes. This theory-driven understanding will provide the basis for phase 2, where we will draw on experience-based co-design methodologies to develop a new, group-based care model for young adults (aged <25 years, under the care of adult diabetes services). In phase 3, we will use a researcher-in-residence approach to implement and evaluate the co-designed group clinic model and compare with traditional care. We will employ qualitative (observations in clinics, patient and staff interviews and document analysis) and quantitative methods (eg, biological markers, patient enablement instrument and diabetes distress scale), including a cost analysis. Ethics and dissemination: National Health Service ethics approval has been granted (reference 17/NI/0019). The project will directly inform service redesign to better meet the needs of young adults with diabetes in socioeconomically deprived areas and may guide a possible cluster-randomised trial, powered to clinical and cost-effectiveness outcomes. Findings from this study may be transferable to other long-term conditions and/or age groups. Project outputs will include briefing statements, summaries and academic papers, tailored for different audiences, including people living with diabetes, clinicians, policy makers and strategic decision makers. Registration details: PROSPERO (CRD42017058726).